Look back - Fujimoto, Tatsuki (VIZ Media, LLC, 2022)
"The overly confident Fujino and the shut-in Kyomoto couldn't be more different, but a love of drawing manga brings these two small-town girls together. A poignant story of growing up and moving forward"--Page 4 of cover.